2022
DOI: 10.1007/s11064-022-03743-5
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Responses to Complement Peptide C3a are Highly Context-Dependent

Abstract: Astrocytes perform a range of homeostatic and regulatory tasks that are critical for normal functioning of the central nervous system. In response to an injury or disease, astrocytes undergo a pronounced transformation into a reactive state that involves changes in the expression of many genes and dramatically changes astrocyte morphology and functions. This astrocyte reactivity is highly dependent on the initiating insult and pathological context. C3a is a peptide generated by the proteolytic cleavage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…As noted above, astrocyte reactivity is associated with diverse changes in molecular expression that can vary from mild to pronounced and that are highly context dependent. Increases in the expression of various molecules that have been noted in reactive astrocytes across multiple contexts include GFAP, vimentin, nestin (probably labelling proliferating astrocytes), synemin plectin, α-crystallin B chain, monoaminoxodase-B (MAO-B), heat shock factor binding protein 1, complement C3, lipocalin 2, C-X-C motif chemokine ligand 10, SerpinA3N, LCN2 and others, 20,[95][96][97][98][99][100][101][102][103] but it important to note that no single molecular marker (including GFAP) is an absolute, required and sufficient, indicator of astrocyte reactivity, and no molecular markers have yet been identified that reliably distinguish amongst different reactive astrocyte phenotypes. In the future, rather than look for additional global markers of astrogliosis, it will likely be more useful to look for molecules upregulated by astrocytes in specific contexts and that are associated with specific functions or effects of astrogliosis.…”
Section: Principles Of Astroglial Pathophysiologymentioning
confidence: 99%
“…As noted above, astrocyte reactivity is associated with diverse changes in molecular expression that can vary from mild to pronounced and that are highly context dependent. Increases in the expression of various molecules that have been noted in reactive astrocytes across multiple contexts include GFAP, vimentin, nestin (probably labelling proliferating astrocytes), synemin plectin, α-crystallin B chain, monoaminoxodase-B (MAO-B), heat shock factor binding protein 1, complement C3, lipocalin 2, C-X-C motif chemokine ligand 10, SerpinA3N, LCN2 and others, 20,[95][96][97][98][99][100][101][102][103] but it important to note that no single molecular marker (including GFAP) is an absolute, required and sufficient, indicator of astrocyte reactivity, and no molecular markers have yet been identified that reliably distinguish amongst different reactive astrocyte phenotypes. In the future, rather than look for additional global markers of astrogliosis, it will likely be more useful to look for molecules upregulated by astrocytes in specific contexts and that are associated with specific functions or effects of astrogliosis.…”
Section: Principles Of Astroglial Pathophysiologymentioning
confidence: 99%
“…After IS, damaged cells produce and release cytokines and DAMPs to stimulate receptors of astrocytes and change their phenotype. A few minutes after IS, due to reactive astrocyte proliferation, astrocytes respond to various inflammatory factors (including TGF-α, ciliary neurotrophic factor, IL-1, IL-6, and kallikrein-related peptidase 6) released by ischemic/hypoxic cells, and are subsequently activated and reproduced ( 69 , 70 ). Reactive astrogliosis occurs in the peri-infarct region, and a glial scar is formed to maintain CNS homeostasis and wall off the lesion ( 71 ).…”
Section: Role and Pathway Of Immune Cells In The Inflammatory Respons...mentioning
confidence: 99%